Valorization of Cultural Heritage through the Scan-to-BIM Process –The Berber Oil Mill as a Materiality of a Total Social Fact - Rawen Chetouane; Faten Hussein (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
In the context of increasing digitalization in the construction sector, the emergence of innovative IT paradigms contributing to the virtual valorization of historic buildings enables the optimization of traditional approaches to preserving cultural heritage. In line with pedagogical experiences that rethink past objects and architectural facts by considering their overall complexity, we present a didactic approach for the regeneration of a traditional Berber oil mill located in southern Tunisia, based on the Scan-to-BIM process. This process involves acquiring historical, graphic, and geometric data to model the building in 3D, using a reverse design method. It integrates data from anthropology, history, archaeology, computer science, energetics, and architectural rehabilitation. This model can be refined and incorporated into an HBIM approach, fostering collaboration in heritage valorization while preserving authenticity and the specific context of the region, positioning it as a catalyst for sustainable development.